The complete RF technician's handbook. - Sayre, Cotter W., ....- (New York : Thomson, 1998)
A handbook for the RF or wireless communications beginner, student, experienced technician or ham radio operator. Although meant for those with a prior foundation in electronics, the book provides information on the fundamental and advanced concepts important to the study and application of RF wireless communications. Only circuits found in the majority of modern RF devices are covered, along with test equipment and their applications. Troubleshooting RF, digital and audio circuits down to the component level is heavily stressed. RF voltage and power amplifiers, their classes of operation, configurations, biasing, coupling techniques, frequency limitations, noise and distortion are all included, as well as LC, crystal and RC oscillators. RF modulation and detection methods are explained in detail - AM, FM, PM and SSB - and associated circuits, such as AGC, squelch, selective calling, frequency multipliers, speech processing, mixers, power supplies, AFC, multiplexing, cellular and microwave communication technologies.
Keywords: Radartoepassingen